New spatial cognition tests for mice: passive place avoidance on stable and active place avoidance on rotating arenas - Cimadevilla, J M; Fenton, A A; Bures, J (Brain research bulletin, 2001)
Dry arenas are a convenient tool for assessing the spatial navigation abilities of rodents. In this paper, mice must avoid a punished sector of a dry arena from which they are expelled by a puff of compressed air. The position of the punished sector is defined relative to the coordinate system of the room. In a stable environment the mice can use both extramaze and intramaze landmarks to orient themselves accurately. However, when the shock area is defined by extramaze landmarks, continuous rotation of the arena at 1 rpm makes it impossible to solve the avoidance task using arena-based cues or idiothesis. The avoidance can only be solved by paying attention to extramaze cues. Our protocol tested spatial abilities on stable and rotating arenas. The acquisition of the task was manifested under both conditions by a significant improvement of performance within the first session (short-term memory component) and at the beginning of the 24-h delayed second session (long-term memory component).
Keywords: mozek; chování zvířat; neuropsychologické testy; Space Perception; Maze Learning; paměť; bludiště - učení; Orientation; Avoidance Learning; zvířata; myši; Mice; učení vyhýbat se; Neuropsychological Tests; Male; Brain; orientace; Psychomotor Performance; Memory; Animals; mužské pohlaví; Behavior, Animal; psychomotorický výkon; vnímání prostoru